2013
DOI: 10.1111/jdv.12203
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of inflammatory mediator expression between palmoplantar pustulosis and pompholyx

Abstract: IL-8 and IL-17A, both are increased in PPP tissue, may represent important immunologic mediators that help to differentiate this clinical entity from pompholyx. This study may provide useful clues in distinguishing PPP from pompholyx, as well as helping to understand the pathogeneses of these two diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…This confirms our previous RT-PCR findings in patients with PPP/PPPP which showed an increase in IL-17 gene expression without an increase in IL-23 [ 5 ]. Increase in IL-17 in PPP/PPPP has also been reported by others [ 14 16 ]. In addition, there was no significant difference in CXCL9 and OAS2 (not shown) which are both induced by interferon-gamma.…”
Section: Discussionsupporting
confidence: 84%
“…This confirms our previous RT-PCR findings in patients with PPP/PPPP which showed an increase in IL-17 gene expression without an increase in IL-23 [ 5 ]. Increase in IL-17 in PPP/PPPP has also been reported by others [ 14 16 ]. In addition, there was no significant difference in CXCL9 and OAS2 (not shown) which are both induced by interferon-gamma.…”
Section: Discussionsupporting
confidence: 84%
“…The principal differential diagnosis, both clinically and histopathologically, is pompholyx, which has two phases: vesicle and pustule [50]. A few studies have been published on histopathological differences between PPP and pompholyx [50][51][52][53]. It has also been suggested that the acrosyringium (i.e., intraepidermal duct of the eccrine glands) is the primary site of vesicle/pustule formation in PPP, in comparison with pompholyx, where the acrosyringium is damaged and rupture is secondary to inflammation [51].…”
Section: Histologymentioning
confidence: 99%
“… 98 The inflammation is further driven by the proliferation of inflammatory cytokines such as IL-8 and IL-17. 94 IL-17A is highly expressed in the palms and soles of patients with PPP in comparison to healthy subjects, 89 while interestingly, IL-12 and IL-23 are not significantly expressed in these areas of patients with PPP. These findings imply a more central role for IL-17A in the inflammatory process for PPP compared to IL-12/IL-23, a difference which could have important implications for treatment.…”
Section: Localized Pustular Psoriasismentioning
confidence: 90%
“…Sensitivities to metals have also been cited as precipitating factors in PPP. 90 , 94 The most common metal sensitivity described is to nickel and occurs in 3% of patients with PPP. 83 Other metal allergies described include chrome and cobalt.…”
Section: Localized Pustular Psoriasismentioning
confidence: 99%